2019
DOI: 10.1162/jocn_a_01421
|View full text |Cite
|
Sign up to set email alerts
|

Anodal Transcranial Direct Current Stimulation to the Left Rostrolateral Prefrontal Cortex Selectively Improves Source Memory Retrieval

Abstract: Functional neuroimaging studies have consistently implicated the left rostrolateral prefrontal cortex (RLPFC) as playing a crucial role in the cognitive operations supporting episodic memory and analogical reasoning. However, the degree to which the left RLPFC causally contributes to these processes remains underspecified. We aimed to assess whether targeted anodal stimulation—thought to boost cortical excitability—of the left RLPFC with transcranial direct current stimulation (tDCS) would lead to augmentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 53 publications
2
13
0
Order By: Relevance
“…Thus, the puzzling negative correlation between choice confidence and rRLPFC activity could be simply explained under the assumption that rRLPFC provides the neurocognitive resources that are instrumental for processing value-relevant information during decisions (and/or to compare item values). This resonates with the known involvement of rRLPFC in reasoning ( Desrochers et al, 2015 ; Dumontheil, 2014 ) or memory retrieval ( Benoit et al, 2012 ; Westphal et al, 2019 ).…”
Section: Discussionsupporting
confidence: 73%
“…Thus, the puzzling negative correlation between choice confidence and rRLPFC activity could be simply explained under the assumption that rRLPFC provides the neurocognitive resources that are instrumental for processing value-relevant information during decisions (and/or to compare item values). This resonates with the known involvement of rRLPFC in reasoning ( Desrochers et al, 2015 ; Dumontheil, 2014 ) or memory retrieval ( Benoit et al, 2012 ; Westphal et al, 2019 ).…”
Section: Discussionsupporting
confidence: 73%
“…Thus, the puzzling negative correlation between choice confidence and rRLPFC activity could be simply explained under the assumption that rRLPFC provides the neurocognitive resources that are instrumental for processing value-relevant information during decisions. This resonates with the known involvement of rRLPFC in reasoning (Desrochers et al, 2015; Dumontheil, 2014) or memory retrieval (Benoit et al, 2012; Westphal et al, 2019).…”
Section: Discussionsupporting
confidence: 73%
“…Previous prefrontal tDCS studies mainly targeting the lateral prefrontal cortex (LPFC) region have reported that stimulation can influence a wide range of cognitive functions ranging from low-level attentional processes to higher-order decision making and working memory functions (Boonstra et al, 2016;Westphal et al, 2019) with some conflicting results (Berryhill et al, 2014;Tremblay et al, 2014). However, the impact of tDCS on the cingulate cortex is not clearly understood.…”
Section: Introductionmentioning
confidence: 99%